Efficacy of metformin in pregnant obese women: a randomised controlled trial. Issue 1 (14th January 2015) - Chiswick, Carolyn A; Reynolds, Rebecca M; Denison, Fiona C; Whyte, Sonia A; Drake, Amanda J; Newby, David E; Walker, Brian R; Forbes, Shareen; Murray, Gordon D; Quenby, Siobhan; Wray, Susan; Norman, Jane E
Abstract : Introduction: Increasing evidence suggests obesity has its origins prior to birth. There is clear correlation between maternal obesity, high birthweight and offspring risk of obesity in later life. It is also clear that women who are obese during pregnancy are at greater risk of adverse outcomes, including gestational diabetes and stillbirth. The mechanism(s) by which obesity causes these problems is unknown, although hyperglycaemia and insulin resistance are strongly implicated. We present a protocol for a study to test the hypothesis that metformin will improve insulin sensitivity in obese pregnant women, thereby reducing the incidence of high birthweight babies and other pregnancy complications. Methods and analysis: The Efficacy of Metformin in Pregnant Obese Women, a Randomised controlled (EMPOWaR) trial is a double-masked randomised placebo-controlled trial to determine whether metformin given to obese (body mass index >30 kg/m 2 ) pregnant women from 16 weeks' gestation until delivery reduces the incidence of high birthweight babies. A secondary aim is to test the mechanism(s) of any effect. Obese women with a singleton pregnancy and normal glucose tolerance will be recruited prior to 16 weeks' gestation and prescribed study medication, metformin or placebo, to be taken until delivery. Further study visits will occur at 28 and 36 weeks' gestation for glucose tolerance testing and to record anthropometric measurements. Birth weight and other measurements will be recorded at time of delivery. Anthropometry of mother and baby will be performed at 3 months postdelivery. As of January 2014, 449 women had been randomised across the UK. Ethics and dissemination: The study will be conducted in accordance with the principles of Good Clinical Practice. A favourable ethical opinion was obtained from Scotland A Research Ethics Committee, reference number 10/MRE00/12. Results will be disseminated at conferences and published in peer-reviewed journals. Trial registration number: ISRCTN51279843.